ANALISIS PENGGUNAAN METODE ALTMAN DALAM MEMPREDIKSI KEBANGKRUTAN PERUSAHAAN (STUDI PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2012-2014) - Fitri Ayu Ningsih; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the implementation of Altman’s (Z-score) analysis in predicting bancruptcy the plastic and packaging companies that is listed at Indonesia Stock Exchange (IDX) study period of 2012-2014. Data analysis used the method of Altman by used ratio of net working capital to total assets, retained earnings to total assets, earning before interest and tax to total assets, market value of equity to total debt, and sales to total assets. After get the Z-score result, then be classified according to the point of cut-off.This study used secondary data, financial reports (annual report). As for data listed in Indonesia Stock Exchange (IDX) for 3 years from 2012-2014. This study is descriptive research in methods of data collection by documentation, by taking data of the company financial statement. Sampling used a purposive sampling technique with researched 11 compenies for three years.This analysis showed that there were four companies which predicted potentially into bancruptcy next year if there is no progress in its financial position and operating result. They are PT Alam Karya Unggul Tbk, PT Berlina Tbk, PT Indopoly Swakarsa Industry Tbk and PT Siwani Makmur Tbk. While there were five companies which predicted into grey area. They are PT Argha Karya Prima Industry Tbk, PT Asiaplast Industries Tbk, PT Lotte Chemical Titan Tbk, PT Trias Sentosa Tbk and PT Yana Prima Hasta Persada Tbk. There is only two companies in good condition, they are PT Champion Pacific Indonesia Tbk and PT Sekawan Inti Pratama Tbk.Keywords : Bankrupt prediction, financial statement analysis, financial ratio, Altman Methode (Z-Score)